Improving the Mathematical Connection Ability of Middle-School Students through Realistic Mathematics Approach - Hasbi, Muhammad; Lukito, Agung; Sulaiman, Raden; Muzaini, Muhammad (Universitas Negeri Surabaya, 2019)
This present study describes how do the process and results of the development of mathematics teaching based on realistic mathematics education to enhance the mathematical connection ability of Middle-School students. The teaching material development model refers to the 4-D Thiagarajan model which has 4 steps namely defining, designing, developing, and disseminating. This participant is studying distributed to learners from a Middle-School 2 Candi Sidoarjo. The study data were obtained with a validation sheet, an observation sheet of teacher and student activities, a student response questionnaire, and a mathematical connection ability test. The products of this study are the learning plan, student worksheets, and mathematical connection ability tests. The results showed that the learning material fulfilled the validity, practical and effective. The results of students' mathematical connection ability tests improved based on t-tests correlated and N-gain analysis. Therefore, it is possible to say that the development of mathematics teaching based on realistic mathematics education can enhance the ability of mathematical connections. As a suggestion, teachers in managing mathematics teaching are very necessary to develop the right tools, so that it has a positive impact on student learning outcomes, especially the ability of students' mathematical connections.Keywords: Realistic Mathematics Education, Mathematical Connection, Middle-School, 4-D Model